2021
DOI: 10.1002/ldr.3977
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different shrub species on their sub‐canopy soil and vegetation properties in semiarid regions

Abstract: Shrubs are one of the most dominant plant types in semiarid ecosystems all over the world. What remains to be investigated is how soil and vegetation characteristics vary under canopy of different species of shrubs in these regions. Thus, this study aimed to compare the effect of three shrub species (Amygdalus scoparia, Ebenus stellata, and Daphne mezereum) on soil and vegetation characteristics under their canopies in semiarid rangelands in Iran for restoration purposes of degraded areas. Fifteen sites were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…Vegetation types differ in nutrient requirements and utilization ability (Yang et al, 2010). The height, canopy surface, and distance from the canopy to the ground of the three studied shrubs have different effects on the soil and plant communities (Erfanzadeh et al, 2021). Many studies have found that shrubs increase soil N, P, and K (Turpin-Jelfs et al, 2019), and SA and LT shrubs also significantly increase soil TN, TP, and TK in the upper soil layer.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Vegetation types differ in nutrient requirements and utilization ability (Yang et al, 2010). The height, canopy surface, and distance from the canopy to the ground of the three studied shrubs have different effects on the soil and plant communities (Erfanzadeh et al, 2021). Many studies have found that shrubs increase soil N, P, and K (Turpin-Jelfs et al, 2019), and SA and LT shrubs also significantly increase soil TN, TP, and TK in the upper soil layer.…”
Section: Discussionmentioning
confidence: 88%
“…Studies in the northern grasslands of China have shown that shrub encroachment reduces the herbaceous abundance and aboveground biomass and that shrub type and climate are dominant factors (Zhou et al, 2019). Erfanzadeh also found that shrub type was an essential factor affecting shrub understory herbaceous communities' productivity and species diversity in semiarid regions (Erfanzadeh et al, 2021). Shrub height and leaf characteristics significantly influence the vegetation characteristics and soil properties of the shrub understory .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bushes have been reported to often facilitate annual forbs (Rodríguez‐Echeverría & Pérez‐Fernández, 2003). According to Erfanzadeh et al (2021), bushes increase the diversity of forbs, possibly due to shading effects on reducing evapotranspiration and enhancing soil moisture for drought‐sensitive species in semiarid areas. Forbs do not usually contribute much to biomass production in grasslands, although they make a significant contribution to the overall plant species diversity (Van Oudtshoorn, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Herbaceous species, such as C. dieterlenii, C. lyrata, B. humilis , P. sphacelatum and P. luteo‐album , grew well in areas under bush canopy but with a low density of bushes. This suggests that these species are shade‐loving and their growth is enhanced when the canopy of the bushes is wide (Erfanzadeh et al, 2021), although they may be outcompeted when the bushes are at a high density.…”
Section: Discussionmentioning
confidence: 99%